2008
DOI: 10.1159/000117172
|View full text |Cite
|
Sign up to set email alerts
|

Parapneumonic Pleural Effusion and Empyema

Abstract: At least 40% of all patients with pneumonia will have an associated pleural effusion, although a minority will require an intervention for a complicated parapneumonic effusion or empyema. All patients require medical management with antibiotics. Empyema and large or loculated effusions need to be formally drained, as well as parapneumonic effusions with a pH <7.20, glucose <3.4 mmol/l (60 mg/dl) or positive microbial stain and/or culture. Drainage is most frequently achieved with tube thoracostomy. The use of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
73
0
21

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(94 citation statements)
references
References 96 publications
0
73
0
21
Order By: Relevance
“…Yet, treatement of patients with pleural infection by medical thoracoscopy may save money comparing to surgery, since the technique is less expensive [11,12] and better tolerated than VATS, which requires tracheal intubation [11]. However, its use in this patient population depends very much on local expertise [11,13].…”
Section: Discussionmentioning
confidence: 99%
“…Yet, treatement of patients with pleural infection by medical thoracoscopy may save money comparing to surgery, since the technique is less expensive [11,12] and better tolerated than VATS, which requires tracheal intubation [11]. However, its use in this patient population depends very much on local expertise [11,13].…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6] Pleural effusions from pneumonia or uremic pleuritis typically are exudative by both criteria. [7][8][9][10][11][12][13][14][15] In addition, transudative effusions as a result of CHF or CO are paucicellular with low neutrophil counts. Pleural effusions resulting from pneumonia or uremic pleuritis have a higher TNC and ANC and higher protein and LDH concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…The PFA in a typical parapneumonic pleural effusion is an exudate by both protein and LDH criteria and is further characterized by elevated nucleated cell counts, particularly neutrophils in the acute phase, and a tendency to lower pH and glucose values than in the typical hydrostatic pleural effusion. [10][11][12][13][14][15] We found that all PFA parameters were affected by the presence of pneumonia in patients at risk for hydrostatic pleural effusion when looked at as a group. However, in eight of the 30 patients with PCHF, the pleural effusions remained transudates by protein and suspected diagnosis of coexisting pneumonia, which is clinically relevant because the differentiation of pulmonary parenchymal opacities on standard chest radiographs in patients in CHF is problematic.…”
Section: Esrd With Co or Chfmentioning
confidence: 99%
“…A question among others is whether those patients should undergo early thoracoscopy or classic treatment. Early thoracoscopy is effective and less invasive than thoracotomy, and was shown to provide significant benefit compared with classic treatment in two small, non-blinded, randomised studies (37)(38)(39)(40). Also, early minimal intervention with pleuroscopy ( Figure 2) has shown excellent results in recent reports.…”
Section: Research In the Understanding And Treatment Of Pleural Diseasesmentioning
confidence: 98%